Plasma and Erythrocyte Glutathione Peroxidase Activity, Serum Selenium Concentration, and Plasma Total Antioxidant Capacity in Cats with IRIS Stages I–IV Chronic Kidney Disease. (16th December 2013) - Krofič Žel, M.; Tozon, N.; Nemec Svete, A.
<x xml:space="preserve">Abstract</x> Background Serum selenium concentrations and the activity of plasma glutathione peroxidase (GPx) decrease with the progression of chronic kidney disease (CKD) in human patients. Selenium is considered a limiting factor for plasma GPx synthesis. Plasma total antioxidant capacity (TAC) is decreased in CKD cats in comparison to healthy cats. Hypothesis Serum selenium concentrations and plasma and erythrocyte GPx activity in cats with CKD are lower than in healthy cats. Serum selenium concentrations, the activity of enzymes, and plasma TAC progressively decrease with the progression of kidney disease according to IRIS (International Renal Interest Society) classification. Animals Twenty‐six client‐owned cats in IRIS stages I–IV of CKD were compared with 19 client‐owned healthy cats. Methods A CBC, serum biochemical profile, urinalysis, plasma and erythrocyte GPx activity, serum selenium concentration, and plasma TAC were measured in each cat. Results Cats in IRIS stage IV CKD had a significantly higher (P = .025) activity of plasma GPx (23.44 ± 6.28 U/mL) than cats in the control group (17.51 ± 3.75 U/mL). There were no significant differences in erythrocyte GPx, serum selenium concentration, and plasma TAC, either among IRIS stages I–IV CKD cats or between CKD cats and healthy cats. Conclusions and Clinical Importance Erythrocyte GPx activity, serum selenium concentration, and plasma TAC do not change in CKD cats compared with healthy cats. Selenium is not a limiting factor in feline CKD. Increased plasma GPx activity in cats with stage IV CKD suggests induction of antioxidant defense mechanisms. Antioxidant defense systems might not be exhausted in CKD in cats.